Sex chromosome chimerism in heterosexual Sahiwal dizygotic twins - BISWAS, JOYDIP; ROY, PRADIP; SAHOO, AJIT KUMAR (The Indian Journal of Animal Sciences, 2014)
It is inferred from this study that presence of XX and XY cells in heterosexual dizygotic twins produce chimerism. Chimerism may be produced due to vascular anastomoses of foetal membranes during early embryonic life before the critical period of sex differentiation. In this study 60 to 64% pure cell lines were observed in both sexes. With this pure cell lines abnormal development of reproductive organs was found in freemartin heifer.